Characterization of Cu3SbS4 microflowers produced by a cyclic microwave radiation - Aup-Ngoen K. (2014)
Copper antimony sulfide (Cu3SbS4) crystals were produced from mixtures of different molar ratios of CuCl, SbCl3 and thiourea in 40 and 60 ml ethylene glycol (EG) by a 300 W cyclic microwave radiation (CMR) for different lengths of time. In the present research, tetragonal Cu3SbS4 microflowers, characterized by X-ray and electron diffraction including electron microscopy and Raman analyses, were successfully produced in the 40 ml solution containing 2:2:4 molar ratio Cu:Sb:S for 40 cycles. Their UV-visible absorption was studied to determine the energy gap (Eg). A formation mechanism was also proposed to relate with the experimental results. © 2011 Elsevier B.V.